Developing an Injectable Nanofibrous Extracellular Matrix Hydrogel With an Integrin αvβ3 Ligand to Improve Endothelial Cell Survival, Engraftment and Vascularization - Hao, Dake; Liu, Ruiwu; Gao, Kewa; He, Chuanchao; He, Siqi; Zhao, Cunyi; Sun, Gang; Farmer, Diana L.; Panitch, Alyssa; Lam, Kit S.; Wang, Aijun (Frontiers in Bioengineering and Biotechnology, 2020)
Endothelial cell (EC) transplantation via injectable collagen hydrogel has received much attention as a potential treatment for various vascular diseases. However, the therapeutic effect of transplanted ECs is limited by their poor viability, which partially occurs as a result of cellular apoptosis triggered by the insufficient cell-extracellular matrix (ECM) engagement. Integrin binding to the ECM is crucial for cell anchorage to the surrounding matrix, cell spreading and migration, and further activation of intracellular signaling pathways. Although collagen contains several different types of integrin binding sites, it still lacks sufficient specific binding sites for ECs. Previously, using one-bead one-compound (OBOC) combinatorial technology, we identified LXW7, an integrin αvβ3 ligand, which possessed a strong binding affinity and functionality to ECs. In this study, to improve the EC-matrix interaction, we developed an approach to molecularly conjugate LXW7 to the collagen backbone, via a collagen binding peptide SILY, in order to increase EC specific integrin binding sites on the collagen hydrogel. Results showed that in the in vitro 2-dimensional (2D) culture model, the LXW7 treated collagen surface significantly improved EC attachment and survival and decreased caspase 3 activity in an ischemic-mimicking environment. In the in vitro 3-dimensional (3D) culture model, LXW7 modified collagen hydrogel significantly improved EC spreading, proliferation, and survival. In a mouse subcutaneous implantation model, LXW7 modified collagen hydrogel improved the engraftment of transplanted ECs and supported ECs to form vascular network structures. Therefore, LXW7 functionalized collagen hydrogel has shown promising potential to improve vascularization in tissue regeneration and may be used as a novel tool for EC delivery and the treatment of vascular diseases.